2020
DOI: 10.1126/sciadv.aaz4868
|View full text |Cite
|
Sign up to set email alerts
|

NIH peer review: Criterion scores completely account for racial disparities in overall impact scores

Abstract: Previous research has found that funding disparities are driven by applications’ final impact scores and that only a portion of the black/white funding gap can be explained by bibliometrics and topic choice. Using National Institutes of Health R01 applications for council years 2014–2016, we examine assigned reviewers’ preliminary overall impact and criterion scores to evaluate whether racial disparities in impact scores can be explained by application and applicant characteristics. We hypothesize that differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 39 publications
3
81
0
Order By: Relevance
“…These types of peer mentoring networks, while clearly advantageous, afforded privilege and have the potential to exacerbate disparities in regard to academic advancement, tenure and promotion, and federal funding that are seen for women and scholars of color. Given that the majority of K awardees do not secure subsequent large-scale funding (e.g., NIH R01 [26]), and disparities in federal funding for women and scholars of color persist [27,28], it could be beneficial for scholars who systemically face challenges to career achievement to have peer mentoring explicitly provided. Further, others have highlighted the importance of friendship and co-mentorship for women and other individuals who are marginalized within the academy to promote resiliency, address self-doubt, and help navigate professional challenges [29,30].…”
Section: Acknowledgments Limitations and Next Stepsmentioning
confidence: 99%
“…These types of peer mentoring networks, while clearly advantageous, afforded privilege and have the potential to exacerbate disparities in regard to academic advancement, tenure and promotion, and federal funding that are seen for women and scholars of color. Given that the majority of K awardees do not secure subsequent large-scale funding (e.g., NIH R01 [26]), and disparities in federal funding for women and scholars of color persist [27,28], it could be beneficial for scholars who systemically face challenges to career achievement to have peer mentoring explicitly provided. Further, others have highlighted the importance of friendship and co-mentorship for women and other individuals who are marginalized within the academy to promote resiliency, address self-doubt, and help navigate professional challenges [29,30].…”
Section: Acknowledgments Limitations and Next Stepsmentioning
confidence: 99%
“…This study showed that award probability for Black principal investigators (PIs) in 2000-2006 was 55% that of white PIs of similar academic achievement (Ginther et al, 2011). NIH scrambled to study potential reasons for this injustice (Barber et al, 2020;Erosheva et al, 2020). We, as scientists and engineers, wrote editorials and promised to do better.…”
mentioning
confidence: 99%
“…Scholarly analyses have demonstrated that National Institutes of Health (NIH) R01 applications from Black investigators had a lower probability of being funded ( Ginther et al , 2011 ). In line with these findings, it has been shown that the overall R01 award rate for Black applicants is only 55% of the success rate for white applicants ( Erosheva et al , 2020 ). Meanwhile, the conversion rate of NIH Pathway to Independence Awards (K99) to the R00 phase is significantly lower for Black awardees compared with white, multiracial, or Asian awardees ( Pickett, 2018 ).…”
Section: Microaggressions: Chronic Damagementioning
confidence: 56%